About the textbooks “Lithology” and “Sedimentary rocks and methods for their analysis” - A. N. Kolchugin; V. P. Morozov; N. S. Zakharova (Известия высших учебных заведений: Геология и разведка, 2023)
We provide a brief description of two editions by Professor Vitaly Germanovich Kuznetsov, Gubkin Russian State University of Oil and Gas. These include the textbooks “Lithology” and “Sedimentary rocks and methods for their analysis”, which present particular interest in the context of the lack of educational materials on lithology. The reviewed textbooks will be helpful for geology students mastering lithological disciplines and preparing for graduate examinations in discipline 1.6.5. Lithology.